Tetraethylortossilicate plasma thin film with hydrophilic and hydrophobic characteristics: Use on passive mixers - Hernandez, Leonardo Frois; Lima, Roberto da Rocha; Pecoraro, Édison [UNESP]; Rosim-Fachini, Esteban; Silva, Maria Lucia Pereira da (Trans Tech Publications, 2012)
This work aims to obtain plasma thin film composites with hydrophobic/hydrophilic alternated regions, which are useful for the production of miniaturized mixers. These regions were acquired by two different strategies: either the codeposition of TEOS and HFE plasma thin films or the exposition of TEOS plasma films to ultraviolet radiation (UVA and UVC). These films were characterized by several chemical and physical techniques. The refractive indexes vary from 1.4 to 1.7; infrared and photoelectron spectroscopy detect Si-O-Si and CHn species. Silicone-like structures with high or low number of amorphous carbon microparticles and with fluorinated organic clusters were produced. Cluster dimensions were in the 1-5 mm range and they are made of graphite or COF (carbon/oxygen/fluorine) compounds. Scanning electron and optical microscopy showed rough surfaces. Water contact angles were 90º; however, for TEOS films that value changed after 6 hr of UVC exposure. Moreover, after UV exposure, organic polar compounds could be adsorbed in those films and water was not. The passive mixer performance was simulated using the FemLab 3.2® program and was tested with 20 nm thick films on a silicon wafer, showing the capacity of these films to be used in such devices.
Keywords: Micromixers; Plasma deposition; TEOS